Uniaxial fiber Bragg grating accelerometer system with temperature and cross axis insensitivity - Antunes, Paulo (2012)
In this paper we describe the implementation and test of an optical fiber based accelerometer with cross axis insensitivity. The accelerometer uses two matching fiber Bragg gratings which are also responsible by the demodulation of the wavelength encoded information. The accelerometer was tested in a reinforced concrete slab, of a 3-storey building located at the University of Aveiro, Portugal. A maximum error of 0.25% for the slab eigenfrequencies was obtained when compared with the values acquired by an electronic sensor. (C) 2010 Elsevier Ltd. All rights reserved.